2017
DOI: 10.11648/j.ijbmr.20170503.12
|View full text |Cite
|
Sign up to set email alerts
|

Anticoagulant Activity of Rhamnan Sulfate Isolated from Commercially Cultured <i>Monostroma nitidum</i>

Abstract: Abstract:The green seaweed, Monostroma nitidum, is widespread in Japan. In Okinawa Prefecture, the production of seaweed is performed using culture-nets that are seeded artificially. Algae contain a soluble polysaccharide, rhamnan sulfate. To estimate its applicability, the anticoagulant activity of rhamnan sulfate was investigated. Rhamanan sulfate was fractionated by ion-exchange chromatography on a DEAE-sepharose column, and two fractions (A and B) were obtained. Partially hydrolyzed rhamnan sulfates with d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…RS [ 18 , 32 ], discovered in a green seaweed M. nitidum , is a rhamnose-predominant, high-molecular-weight glycan fraction with high sulfation. The RS backbone is primarily composed of repeating units [→3)-α-L-Rhap-(1→, →2)-α-L-Rhap-(1→, and →2,3)-α-L-Rhap-(1→], with significant sulfation occurring at the C4 hydroxyl groups.…”
Section: Resultsmentioning
confidence: 99%
“…RS [ 18 , 32 ], discovered in a green seaweed M. nitidum , is a rhamnose-predominant, high-molecular-weight glycan fraction with high sulfation. The RS backbone is primarily composed of repeating units [→3)-α-L-Rhap-(1→, →2)-α-L-Rhap-(1→, and →2,3)-α-L-Rhap-(1→], with significant sulfation occurring at the C4 hydroxyl groups.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, polycarboxyl ulvans prepared with the same species showed clotting times in the range of 101-227 s, which was 7.7 to 17.9 times higher than native ulvans [267]. In another study, 75 µg/mL of polysaccharide extracted from Monostroma nitidum showed 107%, 120-123%, and 167% higher inhibition activities for APPT, PT, and TT assays, respectively, compared to standard heparin [268]. Polysaccharide from Monostroma angicava was also found to be effective in increasing the clotting time in APPT and TT assays and exhibited good anticoagulant activity in in vitro and in vivo studies [269].…”
Section: Anticoagulant Activitymentioning
confidence: 92%
“…Different kinds of algae contain different types of sulfated glycans, such as fucoidan, a fucose-containing sulfated glycan found in brown algae, and agar and carrageenan found in red algae. In green algae, ulvans are the principal cell wall matrix polysaccharides of the genus Ulva [7], and rhamnan sulfates (RS) are found in the genus Monostroma [8].…”
Section: Introductionmentioning
confidence: 99%
“…Marine sulfated polysaccharides often show anticoagulant activity like that exhibited by heparin. Sulfated glycans from green algae, typically consisting of rhamnose, also show anticoagulant activity [8][9][10][11][12][13][14][15]. RS is also bioactive, exhibiting antioxidative, antihyaluronidase, antitumor, anti-obesity, anti-hypercholesterolemic, anti-hyperglycemic, and anti-diabetes activity [16][17][18].…”
Section: Introductionmentioning
confidence: 99%